Theory and method in the study of religion twenty five years on - Hughes, Aaron W., 1968- (Leiden : BRILL, 2013)
This volume reflects on current debates in the academic study of religion by reprinting select articles form the Brill journal Method and Theory in the Study of Religions, currently in its 25th volume, and asking a group of younger scholars to comment on them.
Theory and method in the study of religion : twenty five years on / Aaron W. Hughes -- Inaugural editorial / Ann Baranowksi and John Morgan -- Part one. Pulling no punches: taking aim at the Eliadean paradigm / Matt Sheedy -- How historical is the history of paradigms? / Robert A. Segal -- Part two. Alleviating the Eliade effect: Neil McMullin's critique of Mircea Eliade's regnant discourse in the study of religion / James B. Apple -- The Encyclopedia of Religion: a critique from the perspective of the history of the Japanese religious traditions / Neil McMullin -- Letters to the editors / Gary L. Ebersole -- Response to G.L. Ebersole's criticism of My critique of the Encyclopedia of Relgions / Neil McMullin -- Part three. Coffee with McCuthceon: a conversation about language, pedagogy and critical pluralism / Rebekka King -- Naming the unnameable? Theological language and the academic study of religion / Russell T. McCutcheon -- Part four. On "belief": a story of protectionism / Craig Martin -- On the transformation of "belief" and the domestication of "faith" in the academic study of religion / Donald Wiebe -- Part five. Who owns culture now? / Emma Cohen -- Who owns culture? / Robert N. McCauley and E. Thomas Lawson -- Part six. Lincoln's clarion call for methodological solipsism / Steven Engler and Mark Q. Gardiner -- Theses on method / Bruce Lincoln -- Part seven. The rewards of redescription: an assessment of Burton Mack's influence on the study of Christian origins / Sarah E. Rollens -- On redescribing Christian origins / Burton L. Mack -- Part eight. Taking a critical turn: reflections on Islamic studies and the relevance of John Wansbrough / Yasmin Merchant -- The implications of, and opposition to, the methods and theories of John Wansbrough / Herbert Berg -- Part nine. "Don't drink the water": women, gender, and the study of religion / Jennifer Hall -- The category of gender in the study of religion / Darlene Juschka -- Part ten. Postmodern critiques still challenge the study of religion / Ella Paldam -- Global perspectives on methodology in the study of religion / Armin W. Geertz.
Print version record.
Includes bibliographical references and index.
Keywords: Religion -- Methodology; Religion -- Study and teaching; Religion -- Methodology; Religion -- Study and teaching; Religion; RELIGION -- Comparative Religion; RELIGION -- Essays; RELIGION -- Reference; Religion -- Methodology; Religion -- Study and teaching; Electronic books; Electronic books; Electronic books